Understanding changes to children's connection to nature during the COVID‐19 pandemic and implications for child well‐being. Issue 1 (13th October 2021) - Friedman, Samantha; Imrie, Susan; Fink, Elian; Gedikoglu, Mina; Hughes, Claire
Abstract: While psychological connection to nature is known to be associated with both pro‐environmental behaviours and well‐being, there is an urgent need to extend this research to consider impacts from the COVID‐19 lockdown period. Examining whether children's connection to nature changed during this period, identifying the drivers of these changes and determining the links between connection to nature and child well‐being can each serve to guide post‐lockdown initiatives to promote children's connection to nature. Three findings emerged from this UK sample of 376 families with young children. First, nearly two thirds of parents reported a change (most typically, an increase) in their child's connection to nature. Explanations for this increase included having more time, increased enjoyment of nature and increased awareness or interest in nature. Second, a third of children whose connection to nature decreased during the pandemic displayed increased problems of well‐being—manifest as either 'acting out' (externalising problems) or sadness/anxiety (internalising problems). Third, an increase in connection to nature during the pandemic was more evident for children from affluent families than for their less affluent peers. While connecting to nature may be an effective means of addressing child problems of well‐being, the divergent findings for children from different family backgrounds indicate that efforts to enhance connection to nature should focus on the barriers experienced by children from less affluent families. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.